PH control as a tool for the synthesis of Ag nanoparticles (NPs) aggregates with plasmonic applications - Cativa, Nancy Maribel (2019)
The degree of aggregation of nanoparticles (NPs) exerts an important influence on the physicochemical properties of a dispersion, like optical absorption and photothermal effect . Hence, the controlled tuning of aggregation can be a valuable tool for the synthesis of NPs systems with specific properties and potential technological applications. The stability and degree of aggregation of Ag NPs in a dispersion depend on the nature of the capping agent and also on the properties of the surrounding medium (pH, ionic strength, polarity, etc.). In this work, we analysed the effect of pH and concentration on the aggregation of silver NPs, capped with a ligand bearing carboxylic acid groups, in aqueous dispersions. We then determined the effect of the size of these aggregates on the optical absorption and photothermal effect of the dispersions.